2017
DOI: 10.1159/000461570
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lipid-Inflammatory-Oxidative Metabolism on Auditory Skills after Hearing Aid Fitting in the Elderly

Abstract: This study aimed to assess whether lipid-inflammatory-oxidative metabolism influences auditory processing skills, and whether they function in changing auditory performance after hearing aid fitting in the elderly. Twelve subjects with bilateral hearing loss were submitted to blood tests (to check their lipid-inflammatory-oxidative metabolism) and auditory processing skill tests. After 3 months of using the hearing aids, their auditory skills were re-evaluated and the data were correlated statistically. Oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Age, infections, inflammation and genetic factors also have been shown to play important roles in atherosclerosis [ 8 , 9 , 10 ]. Various types of studies including cross-sectional studies [ 11 , 12 , 13 ], longitudinal studies [ 14 , 15 , 16 , 17 ] and intervention studies [ 18 , 19 ] have linked hyperlipidemia to hearing loss. However, these investigations, in general, targeted either specific populations (elderly adults or specific occupational workers) [ 12 , 16 , 17 , 18 ] or specific types of hearing loss (presbycusis or sudden sensorineural hearing loss) [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, infections, inflammation and genetic factors also have been shown to play important roles in atherosclerosis [ 8 , 9 , 10 ]. Various types of studies including cross-sectional studies [ 11 , 12 , 13 ], longitudinal studies [ 14 , 15 , 16 , 17 ] and intervention studies [ 18 , 19 ] have linked hyperlipidemia to hearing loss. However, these investigations, in general, targeted either specific populations (elderly adults or specific occupational workers) [ 12 , 16 , 17 , 18 ] or specific types of hearing loss (presbycusis or sudden sensorineural hearing loss) [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of studies including cross-sectional studies [ 11 , 12 , 13 ], longitudinal studies [ 14 , 15 , 16 , 17 ] and intervention studies [ 18 , 19 ] have linked hyperlipidemia to hearing loss. However, these investigations, in general, targeted either specific populations (elderly adults or specific occupational workers) [ 12 , 16 , 17 , 18 ] or specific types of hearing loss (presbycusis or sudden sensorineural hearing loss) [ 11 , 13 ]. Additionally, many of these studies included self-reported results for some or all measures (categorical variables) and may lead to the loss of original data and incorporate additional bias [ 16 ].…”
Section: Introductionmentioning
confidence: 99%